THE IMPORTANCE OF GEOGEBRA IN ENHANCING STUDENTS’ LEARNING OF MATHEMATICS AT SCHOOLS - Kuchkarova, Arofathon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
Currently, various interactive teaching methods are being used to increase students' interest in the subject of mathematics. Computer programs integrated into education worldwide are proving to be successful. This article provides brief information about the benefits of using GeoGebra in teaching and learning mathematics. Utilizing GeoGebra's software support in teaching and learning mathematics helps to enhance students' interest in the subject, fosters critical thinking and problem-solving skills, facilitates analysis, and develops cognitive and creative abilities.